Թվային դիվանագիտություն. հնարավորություններ և հեռանկարներ - Մկրտչյան Հայկուհի (YSU Journal of International Affairs, 2016)
The rapid development of information and communication technologies as a result of the global development of the information society inevitably affects the state of society and in all areas, including foreign policy. Currently, many countries in the field of foreign policy and diplomacy are widely using digital applications. In the context of new challenges, new requirements aimed at strengthening the soft power in various fields of cooperation are needed in the field of the foreign policy of Armenia.